1985
DOI: 10.1128/aac.28.5.612
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial activities and subacute toxicity of RC-12, a 4-amino-substituted pyrocatechol

Abstract: RC-12 [1,2-dimethoxy-4-(bis-diethylaminoethyl)-amino-5-bromobenzeneI was evaluated for prophylactic, radical curative, and suppressive activities against infections with Plasmodium cynomolgi and subacute toxicity in rhesus monkeys. Applied as a prophylactic agent, RC-12, administered in doses of 6.25 to 25.0 mg/kg daily throughout the incubation period, provided near-complete to complete protection against 105 to 106 times the minimum infective dose of sporozoites. Applied as a suppressive agent, daily doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…It is known that 25 mg/kg po prevented the development and/or maturation of exoerythrocytic stages in P. cynomolgi , thus showing causal prophylaxis. , Schmidt et al reported that even at 6.25 mg/kg the efficacy did not decrease significantly. Nevertheless, as a result of limited activity against blood stages by 129 , coadministration of chloroquine is required for radical cure …”
Section: Small Molecules Targeting Liver-stage Of Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that 25 mg/kg po prevented the development and/or maturation of exoerythrocytic stages in P. cynomolgi , thus showing causal prophylaxis. , Schmidt et al reported that even at 6.25 mg/kg the efficacy did not decrease significantly. Nevertheless, as a result of limited activity against blood stages by 129 , coadministration of chloroquine is required for radical cure …”
Section: Small Molecules Targeting Liver-stage Of Malariamentioning
confidence: 99%
“…Nevertheless, as a result of limited activity against blood stages by 129, coadministration of chloroquine is required for radical cure. 128 DL-α-Difluoromethylornithine, 130, is a specific irreversible inhibitor of ornithine decarboxylase, a key enzyme in the biosynthesis of polyamines. Compound 130 administered at 1% in drinking water showed prophylactic activity in mice inoculated with P. berghei sporozoites, through the inhibition of early stage exoerythrocytic schizogony.…”
Section: Plasmodium Liver Stagesmentioning
confidence: 99%
“…A second chemical class with modest anti-relapse activity in the P. cynomolgi rhesus model is RC-12. 56 RC-12 is an electron rich ring with amine side chains; interestingly, an overlay with primaquine ( Fig. 5) is apparent and putative metabolites of RC-12 can theoretically form iminoquinones.…”
Section: Next-generation 8-aminoquinolinesmentioning
confidence: 97%
“… 13 Compound 1 ( Figure 1 ) is about 1 order of magnitude less effective than primaquine in this model, but it is also 1 order of magnitude less toxic and produced no hemolysis. 14 However, in a small-scale clinical trial where volunteers were infected with mosquito-borne P. vivax sporozoites, 1 did not prevent infections or inhibit relapses of P. vivax . 15 In this trial, volunteers were given a well-tolerated 7-day course of 1 at 10 mg/(kg day), a dose regimen comparable to that which protected against and cured P. cynomolgi infections in the rhesus monkey model.…”
Section: Introductionmentioning
confidence: 99%
“… 15 In this trial, volunteers were given a well-tolerated 7-day course of 1 at 10 mg/(kg day), a dose regimen comparable to that which protected against and cured P. cynomolgi infections in the rhesus monkey model. 14 Clearly, the dichotomy between the lack of efficacy of 1 against P. vivax hypnozoites in humans 15 and the high efficacy of 1 against P. cynomolgi hypnozoites in rhesus monkeys 14 points to the compelling need to better understand both the pharmacokinetic and the pharmacodynamic profile of 1 and to identify potential active metabolites that might explain these apparent species differences. We now describe our work to elucidate the Phase I metabolism using liver microsomes from various species, the pharmacokinetics in rats, and the in vitro liver-stage activity of 1 and its major metabolites.…”
Section: Introductionmentioning
confidence: 99%